2018
DOI: 10.1016/j.endm.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A network model for routing-fault-free wavelength selection in WRONoCs design

Abstract: Emerging technologies in on-chip communication domain bring about new combinatorial optimization problems at design automation. We address the Wavelength Selection Problem in Wavelength-Routed Optical Networks-on-Chip (WRONoCs), where wavelengths act as signal carriers for initiator-to-target communication, so that signals are the least interfering and routing faults are prevented. We present this novel engineering problem and model it as a constrained shortest path on acyclic networks, propose a graph-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The second problem (Nonato et al 2017) comes from the observation that, once the maximum parallelism level is found, it is also of interest to design the WRONoC in the safest way, despite small variations that might occur in the fabrication process. In order to maximize the probability that the device is able to function correctly, the selected wavelengths used as carriers have to be as far as possible one from the other.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The second problem (Nonato et al 2017) comes from the observation that, once the maximum parallelism level is found, it is also of interest to design the WRONoC in the safest way, despite small variations that might occur in the fabrication process. In order to maximize the probability that the device is able to function correctly, the selected wavelengths used as carriers have to be as far as possible one from the other.…”
Section: Discussionmentioning
confidence: 99%
“…In order to maximize the probability that the device is able to function correctly, the selected wavelengths used as carriers have to be as far as possible one from the other. Such problem was approached in (Nonato et al 2017) through a MILP formulation. In this work, we presented a Constraint Logic Programming on Finite Domains (CLP(FD)) program, showed that it has performances competitive with the MILP approach and found that it is easier to modify it to take into consideration further aspects in the WRONoC design.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations